PENYELESAIAN SENGKETA WARIS DENGAN PERJANJIAN PERDAMAIAN MELALUI PEMERINTAH DESA DI KECAMATAN BAE KABUPATEN KUDUS - Normassari, Alifah; Hartanto, Dwiyana Achmad; Wardhani, Lidya Christina (Jurnal Suara Keadilan, 2020)
AbstractThis study aims to determine the settlement of inheritance disputes with a peace agreement through the village government and its obstacles. The approach used is a sociological juridical approach or an empirical legal approach. Data collection techniques by looking for primary data and secondary data, which are related to the subject matter. Data are arranged systematically and then analyzed qualitatively, it can be obtained clarity about the problem that is easily understood by readers. The result of the research obtained is the process of inheritance dispute resolution through the Village Government which uses mediation outside the court in 10 villages in Bae District. It turns out that the object of the dispute that causes the dispute to arise determines how the dispute resolution process is. The obstacles that arise include the difficulty in gathering disputing parties to be present in the mediation process and the peace agreement does not have executorial power.It can be seen that in the 10 villages in Bae District, all of them have problems with the difficulty of the mediation process and the difficulty of gathering parties to participate in the mediation process. . The effort made by the Bae Village Government was that after the mediation result was agreed upon, it was immediately registered with the PPAT.Keywords: Inheritance Dispute Resolution, Peace Agreement, Bae District, Kudus Regency. Abstrak Penelitian ini bertujuan untuk mengetahui penyelesaian sengketa waris dengan perjanjian perdamaian melalui Pemerintah Desa dan kendalanya. Pendekatan yang digunakan adalah pendekatan yuridis sosiologis atau pendekatan hukum empiris. Teknik pengumpulan data dengan mencari data primer dan data sekunder, yang berhubungan dengan pokok permasalahan. Data disusun secara sistematis dan selanjutnya di analisa secara kualitatif, dapat diperoleh kejelasan tentang permasalahan yang mudah dipahami pembaca. Hasil penelitian yang diperoleh adalah proses penyelesaian sengketa waris melalui Pemerintah Desa yang menggunakan mediasi diluar pengadilan di 10 desa yang ada di Kecamatan Bae ternyata objek sengketanya yang menyebabkan timbulnya sengketa menentukan bagaimana proses penyelesaian sengketa. Kendala yang muncul yaitu antara lain sulitnya mengumpulkan para pihak yang bersengketa dapat hadir dalam proses mediasi serta perjanjian perdamaian tidak mempunyai kekuatan eksekutorial dapat dilihat pada 10 desa yang ada di Kecamatan Bae semua mempunyai kendala pada alotnya proses mediasi dan sulitnya mengumpulkan para pihak untuk mengikuti proses mediasi. Upaya yang dilakukan oleh Pemerintahan Desa Bae adalah setelah disepakati hasil mediasi maka langsung didaftarkan kepada PPAT.Kata Kunci: Penyelesaian Sengketa Waris, Perjanjian Perdamaian, Kecamatan Bae Kabupaten Kudus.